Big week the biggest air battle of World War II - Holland, James 1970- (Atlantic Monthly Press, 2018)
During the third week of February 1944, the combined Allied air forces based in Britain and Italy launched their first round-the-clock bomber offensive against Germany. Their goal: to smash the main factories and production centers of the Luftwaffe while also drawing German planes into an aerial battle of attrition to neutralize the Luftwaffe as a fighting force prior to the cross-channel invasion, planned for a few months later. Officially called Operation ARGUMENT, this aerial offensive quickly became known as 'Big Week,' and it was one of the turning-point engagements of World War II.
Keywords: United States / Army Air Forces / History / World War, 1939-1945; Great Britain / Royal Air Force / History / World War, 1939-1945; Germany / Luftwaffe / History / World War, 1939-1945; Germany / Luftwaffe; Great Britain / Royal Air Force; United States / Army Air Forces; World War (1939-1945); World War, 1939-1945 / Aerial operations; World War, 1939-1945 / Campaigns / Western Front; Military campaigns; Military operations, Aerial; Western Front (World War (1939-1945)); HISTORY / Military / General; HISTORY / Military / United States; HISTORY / Europe / Western; 1939-1945; History